Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có \(A=x^3+3.x^2-4=\left(x-1\right)\left(x^2+4x+1\right)\)
Lại có \(\left(x-1\right)\left(x^2+4x+4\right)⋮\left(x^2+4x+4\right)\)
=> \(A⋮\left(x^2+4x+4\right)\)với mọi x
Câu 1:
a) \(\left(x^2+y^2-36\right)^2-4x^2y^2\)
\(=\left(x^2+y^2-36\right)^2-\left(2xy\right)^2\)
\(=\left(x^2+y^2+2xy-36\right)\left(x^2+y^2-2xy-36\right)\)
\(=\left[\left(x+y\right)^2-36\right]\left[\left(x-y\right)^2-36\right]\)
\(=\left(x+y+6\right)\left(x+y-6\right)\left(x-y+6\right)\left(x-y-6\right)\)
b) \(\left(x^2+x\right)^2-5\left(x^2+x\right)+6\)
\(=\left(x^2+x\right)^2-2\left(x^2+x\right)-3\left(x^2+x\right)+6\)
\(=\left(x^2+x\right)\left(x^2+x-2\right)-3\left(x^2+x-2\right)\)
\(=\left(x^2+x-3\right)\left(x^2+x-2\right)\)
\(=\left(x^2+x-3\right)\left(x-2\right)\left(x+1\right)\)
1) a) (x2 + y2 - 36)2 - 4x2y2
= (x2 + y2 - 36 - 2xy)(x2 + y2 - 36 + 2xy)
= [(x - y)2 - 36][(x + y)2 - 36]
= (x - y - 6)(x - y + 6)(x + y + 6)(x + y - 6)
b) (x2 + x)2 - 5(x2 + x) + 6
= (x2 + x)2 - 2(x2 + x) - 3(x2 + x) + 6
= (x2 + x)(x2 + x - 2) - 3(x2 + x - 2)
= (x2 + x - 3)(x2 + 2x - x - 2)
= (x2 + x - 3)(x - 1)(x + 2)
2) Đặt tính là đc
\(4x^2+3x+a=4x\left(x+3\right)-9\left(x+3\right)+27+a=\left(x+3\right)\left(4x-9\right)+27+a⋮x+3\)
\(\Rightarrow27+a=0\Rightarrow a=-27\)
\(4x^2+3x+a⋮x+3\\ \Leftrightarrow4x^2+3x+a=\left(x+3\right)\cdot a\left(x\right)\)
Thay \(x=-3\)
\(\Leftrightarrow4\cdot9-9+a=0\\ \Leftrightarrow27+a=0\\ \Leftrightarrow a=-27\)